Directed information panspermia as a possible method of interstellar communication - Kocharyan, Sh. M. (Frontiers in Astronomy and Space Sciences, 2026)
The problem of transmitting an interstellar message from one communicative civilization to another is examined, taking into account possible scenarios for the prevalence of civilizations in the Galaxy, including the possibility that Earth’s civilization is unique. I propose the hypothesis of Directed Information Panspermia (DIP), according to which a sending civilization, aiming to transmit a message to a future civilization, may undertake two simultaneous actions: (1) introduce artificially synthesized primitive life forms onto planets favorable for the development of life and intelligence, from which communicative civilizations may subsequently emerge through biological evolution; and (2) encode the transmitted message on a carrier capable of preserving information for the timescale required for the emergence of the recipient civilization. These two actions can be unified by using the biological structures of the introduced life forms—in particular the genetic code of terrestrial-type organisms—as the message carrier. This approach suggests that the genetic code, in addition to its biological function, may also serve a supra-biological role as an interstellar information medium.